Reading Girls' Literature: Popular Finnish Heroine Tiina - Kokkonen Sara (Vilnius University, 2022)
The Tiina book series for girls circulated in Finland for a considerable period of thirty years (1956–1986). This girls’ series was quite popular among young girls during the whole period, and the protagonist Tiina has appealed to young Finnish readers for decades. Different generations have read the girls’ books about the brave and tomboy heroine. Girls’ series books are part of the girls’ literature genre, which was developed originally in the mid-nineteenth century. This article explores the reading and reception of Tiina books in the context of the Finnish and international girls’ literature and reading research. Female readers of various ages participated in a reading survey and submitted written accounts of their experiences reading the Tiina books. In particular, this article seeks to examine the engagement of readers with the books and the girl protagonist.